Internal aeration of paddy field rice (Oryza sativa) during complete submergence - importance of light and floodwater O2. - Winkel, Anders; Colmer, Timothy D.; Ismail, Abdelbagi M.; Pedersen, Ole (Wiley, 2013)
Flash floods can submerge paddy field rice (Oryza sativa), with adverse effects on internal aeration, sugar status and survival. Here, we investigated the in situ aeration of roots of rice during complete submergence, and elucidated how underwater photosynthesis and floodwater pO2 influence root aeration in anoxic soil. In the field, root pO2 was measured using microelectrodes during 2 d of complete submergence. Leaf gas films that formed on the superhydrophobic leaves were left intact, or experimentally removed, to elucidate their effect on internal aeration. In darkness, root pO2 declined to very low concentrations (0.24 kPa) and was strongly correlated with floodwater pO2. In light, root pO2 was high (14 kPa) and primarily a function of the incident light determining the rates of underwater net photosynthesis. Plants with intact leaf gas films maintained higher underwater net photosynthesis relative to plants without gas films when the submerged shoots were in light. During complete submergence, internal aeration of rice in the field relies on underwater photosynthesis during the day and entry of O2 from the floodwater during the night. Leaf gas films enhance photosynthesis during submergence leading to improved O2 production and sugar status, and therefore contribute to the submergence tolerance of rice.Flash floods can submerge paddy field rice (Oryza sativa), with adverse effects on internal aeration, sugar status and survival. Here, we investigated the in situ aeration of roots of rice during complete submergence, and elucidated how underwater photosynthesis and floodwater pO2 influence root aeration in anoxic soil.In the field, root pO2 was measured using microelectrodes during 2 d of complete submergence. Leaf gas films that formed on the superhydrophobic leaves were left intact, or experimentally removed, to elucidate their effect on internal aeration.In darkness, root pO2 declined to very low concentrations (0.24 kPa) and was strongly correlated with floodwater pO2. In light, root pO2 was high (14 kPa) and primarily a function of the incident light determining the rates of underwater net photosynthesis. Plants with intact leaf gas films maintained higher underwater net photosynthesis relative to plants without gas films when the submerged shoots were in light.During complete submergence, internal aeration of rice in the field relies on underwater photosynthesis during the day and entry of O2 from the floodwater during the night. Leaf gas films enhance photosynthesis during submergence leading to improved O2 production and sugar status, and therefore contribute to the submergence tolerance of rice.